Dec1 Deficiency Ameliorates Pulmonary Fibrosis Through the PI3K/AKT/GSK-3β/β-Catenin Integrated Signaling Pathway - Hu, Xingxing; Zou, Menglin; Ni, Lan; Zhang, Mingyang; Zheng, Weishuai; Liu, Bing; Cheng, Zhenshun (Frontiers in Pharmacology, 2022)
Tissue remodeling/fibrosis is a main feature of idiopathic pulmonary fibrosis (IPF), which results in the replacement of normal lung parenchyma with a collagen-rich extracellular matrix produced by fibroblasts and myofibroblasts. Epithelial-mesenchymal transition (EMT) in type 2 lung epithelial cells is a key process in IPF, which leads to fibroblasts and myofibroblasts accumulation and excessive collagen deposition. DEC1, a structurally distinct class of basic helix-loop-helix proteins, is associated with EMT in cancer. However, the functional role of DEC1 in pulmonary fibrosis (PF) remains elusive. Herein, we aimed to explore DEC1 expression in IPF and bleomycin (BLM)-induced PF in mice and the mechanisms underlying the fibrogenic effect of DEC1 in PF in vivo and in vitro by Dec1-knockout (Dec1−/−) mice, knockdown and overexpression of DEC1 in alveolar epithelial cells (A549 cells). We found that the expression of DEC1 was increased in IPF and BLM-injured mice. More importantly, Dec1−/− mice had reduced PF after BLM challenge. Additionally, DEC1 deficiency relieved EMT development and repressed the PI3K/AKT/GSK-3β/β-catenin integrated signaling pathway in mice and in A549 cells, whereas DEC1 overexpression in vitro had converse effects. Moreover, the PI3K/AKT and Wnt/β-catenin signaling inhibitors, LY294002 and XAV-939, ameliorated BLM-meditated PF in vivo and relieved EMT in vivo and in vitro. These pathways are interconnected by the GSK-3β phosphorylation status. Our findings indicated that during PF progression, DEC1 played a key role in EMT via the PI3K/AKT/GSK-3β/β-catenin integrated signaling pathway. Consequently, targeting DEC1 may be a potential novel therapeutic approach for IPF.